Numerical Study of the Upgraded Hot Zone in Silicon Directional Solidification Process. Issue 2 (6th January 2021) - Su, Wenjia; Yang, Wei; Li, Jiulong; Han, Xiaomin; Wang, Junfeng
Abstract: 2D global transient model for generation‐six (G6) GT‐style furnace and upgraded generation‐seven (G7) ALD‐style furnace in which all types of heat transfer and flow are included is established to investigate the thermal field, melt convection, melt–crystal (m–c) interface shape, thermal stress, growth rate, and Voronkov ratios in the growing silicon ingot. The modeling is verified by the heater power and temperature experiment. Simulation results show that the melt flow is relatively stronger as the furnace upgrades. For G7, a relatively higher thermal stress and growth rate are found due to the higher temperature gradient both in the horizontal and axial directions. Furthermore, unlike the optimized G6, G7 shows the overly convex m–c interface in the initial stage and edge nucleation throughout crystal growth stage. Abstract : 2D global transient model for G6 GT‐style furnace (G6) and upgraded G7 ALD‐style furnace (G7) is established and compared. The melt flow intensity is relatively stronger as the furnace upgrades. The over‐convex phenomenon of melt–crystal interface is found in the initial stage of G7. G7 shows relatively higher thermal stress and Voronkov ratios due to higher temperature gradient.